Histopathological alterations of gonads in teleosts - KOKOKIRIS (Λ. ΚΟΚΟΚΥΡΗΣ) L.; RAGIAS (Β. ΡΑΓΙΑΣ) V.; ATHANASSOPOULOU (ΑΘΑΝΑΣΟΠΟΥΛΟΥ Φ.) F. (Journal of the Hellenic Veterinary Medical Society, 2017)
A systematic presentation of various histological changes in teleosts gonads is presented, as well as the pathological changes caused by environmental stress. Under conditions of environmental stress (e.g. pollution) or even inappropriate environmental conditions, the gonadal histological changes include the expansive atresia, the modification of characteristics of ovogenesis (size and intensity of pigmentation of lipid globules), the necrosis of sperm, the proliferation of Sertoli cells, the presence of brown-yellow bodies, parasites, neoplasias and gonadal cysts. The knowledge of histological changes can be very useful for the identification of factors affecting the reproductive health of fish populations and the way they affect them.